New journalism: solutions oriented journalism - Domazet Daničič, Sanja; Vukadinović, Maja (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Journalism aimed at reflection and  finding solutions to social problems is expanding at a time when the world is facing numerous challenges such as the reduction of financial resources and a potential economic crisis, climate change, the consequences of a global pandemic and pronounced social inequality. The text examines the scope and application of solution oriented journalism in the context of the new social role of journalists, which is reflected in inspiring citizens to fight for change, raising awareness of social irregularities and encouraging action. The possibilities and scope of socially responsible journalism are analyzed. The goal of the paper is to point out the real scope of modern journalism, which should identify problems and conflicts in the community and provide appropriate solutions. The paper examines the specifics of solution oriented journalism in relation to related journalistic approaches and analyzes the ways in which stories are structured within this approach. An analysis of the application of solution oriented journalism in journalistic practice in Serbia was conducted. The method used for the research is an in-depth interview. The conducted research indicates that professional journalism in Serbia faces numerous challenges and that few journalists have enough knowledge, resources, support and willingness to initiate solutions in complex social circumstances. The conclusion is that complete changes are necessary in society and in the profession itself, so that more journalists in Serbia are directed towards in-depth research into solutions.